A STUDY OF THE SEMANTIC FEATURES OF EXPLICIT JUDGEMENTS IN POLITICAL SPEECHES IN AMERICAN ENGLISH - Nguyễn Thanh Tâm (2014)
Introduction; Literature review and theoretical background; Research methodology; ...